Arctiin inhibits adipogenesis in 3T3-L1 cells and decreases adiposity and body weight in mice fed a high-fat diet - Min, Byulchorong; Lee, Heejin; Song, Ji Hye; Han, Myung Joo; Chung, Jayong (Nutrition research and practice, 2014)
The purpose of this study was to examine the effects and associated mechanisms of arctiin, a lignan compound found in burdock, on adipogenesis in 3T3-L1 cells. Also, the effects of arctiin supplementation in obese mice fed a high-fat diet on adiposity were examined. 3T3-L1 cells were treated with arctiin (12.5 to 100 µM) during differentiation for 8 days. The accumulation of lipid droplets was determined by Oil Red O staining and intracellular triglyceride contents. The expressions of genes related to adipogenesis were measured by real-time RT-PCR and Western blot analyses. For in vivo study, C57BL/6J mice were first fed either a control diet (CON) or high-fat diet (HF) to induce obesity, and then fed CON, HF, or HF with 500 mg/kg BW arctiin (HF + AC) for four weeks. Arctiin treatment to 3T3-L1 pre-adipocytes markedly decreased adipogenesis in a dose-dependent manner. The arctiin treatment significantly decreased the protein levels of the key adipogenic regulators PPARγ and C/EBPα, and also significantly inhibited the expression of SREBP-1c, fatty acid synthase, fatty acid-binding protein and lipoprotein lipase. Also, arctiin greatly increased the phosphorylation of AMP-activated protein kinase (AMPK) and its downstream target phosphorylated-acetyl CoA carboxylase. Furthermore, administration of arctiin significantly decreased the body weight in obese mice fed with the high-fat diet. The epididymal, perirenal or total visceral adipose tissue weights of mice were all significantly lower in the HF + AC than in the HF. Arctiin administration also decreased the sizes of lipid droplets in the epididymal adipose tissue. Arctiin inhibited adipogenesis in 3T3-L1 adipocytes through the inhibition of PPARγ and C/EBPα and the activation of AMPK signaling pathways. These findings suggest that arctiin has a potential benefit in preventing obesity.